Exploring the Significance of Mahabbah in QS. Ali ‘Imran [3]: 31 and Its Connection to the Tradition of Reciting Shalawat, Particularly in South Sumatra - Nugroho, Nugroho; Zulfikar, Eko; Mardiah, Anisatul (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
This article aims to find out the relevance of the meaning of mahabbah in QS. Ali 'Imran [3]: 31 with the tradition of reciting blessings in Belitang OKU East South Sumatra. This is motivated by a tradition that has developed in the community in the form of reciting prayers in an assembly called Shalawat Pendowo Limo. While the motivation for the establishment of the Islamic Prayer Council was to introduce the figure of the Prophet to the general public, especially to the younger generation with the aim of making them love and emulate the Prophet more. By using qualitative methods and types of library research, by tracing data in the form of written sources which are corroborated by interview results, this study concludes that: first, mahabbah in QS. Ali 'Imran [3]: 31 means the feeling of love for Allah which is proven by obeying all His commands and following the revelations or teachings revealed to His Prophet Muhammad SAW. The love for Allah is incomplete if you do not also love the Prophet Muhammad by proving that he always prays for him. Second, the meaning of mahabbah in QS. Ali 'Imran [3]: 31 is very relevant to the goals and motivations for praying for the Belitang OKU East Sumatra community. The proof of this mahabbah can be seen from the hope of increasing love for the Prophet Muhammad SAW and hope for Allah so that one day he will get the Prophet's intercession on the Day of Judgment by praying to him. Even though it is not certain that everyone who recites prayers loves Allah and His Messenger, at least efforts to love Allah and His Messenger can be instilled with joint prayers through the Shalawat Pendowo Limo Assembly.